Radiochemical Analysis of Pu, U and Sr Isotopes in Soil Samples with Anion Exchange, UTEVA, Strontium Resin - Lee, M.H.; Park, J.H.; Lee, C.H.; Song, K. (Asian Journal of Chemistry, 2012)
This study presents a rapid and quantitative sequential radiochemical separation method for the Pu, U and Sr isotopes with an anion exchange resin, UTEVA resin and Sr resin in soil samples. After the radionuclides were leached from samples with 8M HNO3, the Pu, U and Sr isotopes were sequentially adsorbed on the anion exchange column, UTEVA column connected with Sr Spec column. The Pu isotopes were purified from other nuclides through the anion exchange column and the uranium isotopes were separated from other nuclides through the UTEVA column. Also, 90Sr was separated from other hindrance elements with the Sr Spec column. After a source preparation for the purified Pu and U with the micro-coprecipitation method, the Pu and U were measured by an a-spectrometry. Strontium-90 was measured by a low level liquid scintillation counter. The radiochemical procedure for Pu, U and Sr nuclides investigated in this study has been validated by application to IAEA reference soils.